Efficacy of a brief intervention based on an Incremental Theory of Personality in the prevention of adolescent dating violence : a randomized controlled trial - Fernández González, Liria (Colegio Oficial de Psicólogos de Madrid, 2020)
New intervention approaches are required for dating violence (DV) prevention, given the limited results of existing programs in achieving behavioral changes. The main objective of this study was to explore the effect of a brief, single- session intervention aimed at promoting an incremental theory of personality (ITP) on dating violence perpetration (DVP) and dating violence victimization (DVV). A double-blind randomized controlled trial (RCT) with two parallel groups (experimental vs. control) was conducted. Participants were 123 adolescents (53.7% females, Mage = 15.20, SD = 0.99). Assessment measures were administered one week prior to the intervention, and six months and one year after the intervention. The results of the hierarchical linear models showed that the interaction between time and condition was statistically significant for DVP, showing a significant decrease both in traditional and cyber dating abuse in the experimental condition. The ITP intervention had no effect on DVV. Our findings suggest that the ITP intervention decreases the perpetration of aggressive acts toward the dating partner and support the idea that strategies aimed at preventing peer conflict may also prevent DVP. Increasing our empirical evidence about the efficacy of a one-hour self- applied intervention is of great relevance for moving forward in the prevention of DV.